DFT, PM3, AM1, and MINDO/3 Quantum Mechanical Calculations for Some INHC Cs Symmetry Schiff Bases as Corrosion Inhibitors for Mild Steel - Rehab Majed Kubba; Fatin Kareem Abood (Application of Quantum Mechanical Calculations and Symmetry in Chemistry; Vibration Frequencies, Corrosion Inhibition and Prodrugs, 2021)
Density Functional Theory (DFT) at the B3LYP/ 6-311G basis set level and semiemperical methods (PM3, AM1, and MINDO/3) were performed on six new substituted Schiff bases derivatives of INHC (N-(3-(phenylidene-allylidene) isonicotinohydrazide) using Gaussian-03 program. The calculated quantum chemical parameters correlated to the inhibition efficiency were studied and discussed at their equilibrium geometry and their correct symmetry (Cs). Comparisons of the order of inhibition efficiency of the Schiff bases derivatives, and local electrophilic and nucleophilic reactivity have analyzed. Some physical properties also were studied such as heat of formation, total energy and dipole moment...etc. Also vibration frequencies and IR absorption intensities were carried out for the calculated Schiff bases molecules.